2009
DOI: 10.1007/s10508-008-9467-1
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Body Esteem and Sexual Desire Among College Women

Abstract: Relationships between body image variables and sexuality have been found among several groups of women. However, research has largely focused on generalized experiences of sexuality. With the exception of two studies which focused on specific medical populations, to our knowledge there has been no investigation of the relationship between body image and acute measures of sexual response. In the current study, we investigated the relationships between body esteem, sexual response to erotica in a laboratory-sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(66 citation statements)
references
References 38 publications
5
58
0
2
Order By: Relevance
“…Appearance dissatisfaction has been shown to predict decreased sexual satisfaction in women (Hoyt & Kogan,2001;LaRocque&Cioe,2011;Weavers&Byers,2013).Itis also associated with decreased sexual function (Pauls, Occhino, & Dryfhout, 2008), including lower sexual desire, lowered propensity to orgasm, poorer subjective sexual arousal, and decreased lubrication (Koch,Mansfield, Thurau, & Carey, 2005;Sanchez& Kiefer, 2007;Seal, Bradford, & Meston, 2009;Seal & Meston 2007).…”
Section: Body Image and Sexual Healthmentioning
confidence: 99%
“…Appearance dissatisfaction has been shown to predict decreased sexual satisfaction in women (Hoyt & Kogan,2001;LaRocque&Cioe,2011;Weavers&Byers,2013).Itis also associated with decreased sexual function (Pauls, Occhino, & Dryfhout, 2008), including lower sexual desire, lowered propensity to orgasm, poorer subjective sexual arousal, and decreased lubrication (Koch,Mansfield, Thurau, & Carey, 2005;Sanchez& Kiefer, 2007;Seal, Bradford, & Meston, 2009;Seal & Meston 2007).…”
Section: Body Image and Sexual Healthmentioning
confidence: 99%
“…For example, studies of young women have reported significant associations between negative body image and risky sexual behaviors, including lower probability of using contraceptives and earlier age of first intercourse (Eisenberg, Neumark-Sztainer, & Lust, 2005;Gillen, Lefkowitz, & Shearer, 2006;Pinquart, 2010). In addition, negative body image is associated with women's sexual functioning: women who experience greater anxiety and shame about their bodies have lower levels of sexual desire and arousability (Koch, Mansfield, Thurau, & Carey, 2005;Sanchez & Kiefer, 2007;Seal, Bradford, & Meston, 2009) and report decreased sexual satisfaction (Weaver & Byers, 2006;Yamamiya, Cash, & Thompson, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Por lo tanto, se deduce que la apariencia física de la pareja va a iniciar una respuesta sexual (Seal, Bradford, & Meston, 2009). Se ha encontrado que los hombres tienden a poner más atención al atractivo físico de su pareja como mediador de la relación, mientras que las mujeres toman en cuenta el afecto percibido (Parish, Luo, Stolzenberg, Lauman, Farrer, & Pan, 2007).…”
Section: Introductionunclassified